Moors and Saracens in Europe: estimating the medieval North African male legacy in southern Europe. - Capelli, C; Onofri, V; Brisighelli, F; Boschi, I; Scarnicci, F; Masullo, M; Ferri, G; Tofanelli, S; Tagliabracci, A; Gusmao, L; Amorim, A; Gatto, F; et al. (2009)
To investigate the male genetic legacy of the Arab rule in southern Europe during medieval times, we focused on specific Northwest African haplogroups and identified evolutionary close STR-defined haplotypes in Iberia, Sicily and the Italian peninsula. Our results point to a higher recent Northwest African contribution in Iberia and Sicily in agreement with historical data. southern Italian regions known to have experienced long-term Arab presence also show an enrichment of Northwest African types. The forensic and genomic implications of these findings are discussed.